O processo de adaptação da mulher às modificações da gestação à luz da teoria de Callista Roy. - MELO, Kaliny Mendes (2018)
Being pregnant means facing a large number of biological, psychological and social changes that require important individual adjustments, as well as many other interpersonal ones, it is necessary then that a process of adaptation to these changes occurs, which must be assisted by the professional nurse. The objective of this study was to understand the process of adaptation to motherhood in pregnant women, who perform prenatal care in three health units in São Luís, Maranhão. Qualitative research. The subjects were pregnant in the third trimester of gestation who underwent prenatal follow-up at health units located in the city of São Luís, Maranhão. For data collection we used an interview with semi-structured questions, a form with sociodemographic questions and a field diary. The results were categorized in the adaptive modes of Sister Callista Roy and in the nursing goal according to the author. In the physiological mode the common problems of adaptation to the gestation most found were nausea and vomiting, fatigue, sleep deprivation intolerance to activity, stress, anxiety, edema and pain. In role-playing mode most women reported happiness with the new role. In the interdependence mode the support of family members, partners and friends was fundamental to the well-being of the pregnant woman. In our study, regarding the measures that influenced the adaptation of pregnant women, three scenarios were evident: a) effective nursing consultation in the promotion of adaptation; b) ineffective nursing consultation in the promotion of adaptation; c) group of pregnant women as an efficient mechanism to promote adaptation.